Yield performance of okra under potassium fertilization and number of plants per hole - Rodrigues Silva, Luiz Daniel; Pereira de Oliveira, Ademar; Ferreira de Lima Cruz, José Manoel; Leite de Souza, André Luís; Soares do Nascimento, Izaias Romario (Comunicata Scientiae, 2021)
The okra is a vegetable that responds to mineral nutrition and the plant population, with increased production. The work was carried out at the Federal University of Paraíba, in Areia-PB, with the objective of evaluating the influence of K2O doses and number of plants per pit on the yield and quality of okra, cultivating Santa Cruz, in an experimental block design randomized, with treatments distributed in a 6 x 2 factorial scheme, with six K2O doses (0, 50, 100, 150, 200 and 250 kg ha-1), and one and two plants per pit, in four replications. The values ​​for the average mass of fruits, 16 and 18 g were reached as a function of K2O doses, with one and two plants per pit, respectively. The highest numbers of fruits per plant in okra were 45 and 56, at doses of 123.7 and 184 kg ha-1 of K2O, respectively for one and two plants per pit, and the highest fruit production per plant was 584.2 g, with two plants per pit and 250 kg ha-1 of K2O. The total fruit yield was 42.13 t ha-1, in the treatment with two plants per pit and 100 kg ha-1 of K2O, and the doses of 122.5 and 115 kg ha-1 of K2O were responsible for the higher productivity of commercial fruits in okra, 25.6 and 29.2 t ha-1, respectively, with one and two plants per pit, and the leaf K content was influenced only by K2O doses. Keywords: Abelmoschus esculentus; mineral fertilizers; plant density